'Can' and the Consequence Argument. (10th October 2013) - Grzankowski, Alex
Abstract The consequence argument is a powerful incompatibilist argument for the conclusion that, if determinism is true, what one does is what one must do. A major point of controversy between classical compatibilists and incompatibilists has been over the use of 'can' in the consequence argument. Classical compatibilists, holding that abilities to act are dispositions, have argued that 'can' should be analyzed as a conditional. But such an analysis of 'can' puts compatibilists in a position to grant the premises of the argument while denying the conclusion. Incompatibilists remain unconvinced, and this corner of the debate over free will has reached a dialectical impasse. The present paper has two aims. First, to offer a new dialectical point of entry into this dispute on behalf of incompatibilists. By making use of Angelika Kratzer's influential semantic work on 'can' and 'must', I argue that incompatibilists are in a position to offer a plausible, positive treatment of 'can' that favors their view. Second, even if one does not think incompatibilism is thereby true (for as we shall see there are places to push back), the Kratzer semantics yields a number of important insights concerning the consequence argument that should be of broad interest.1